The costs and value of modelling-based design in healthcare delivery: five case studies from the US. Issue 3 (2nd July 2020) - Young, Terry; Soorapanth, Sada; Wilkerson, Jim; Millburg, Lance; Roberts, Todd; Morgareidge, David
ABSTRACT: In the nineties and noughties, Hollocks surveyed the use of Discrete Event Simulation (DES) in industry and listed (although he could not quantify the value of) benefits. This paper explores how DES is now used to design healthcare facilities and services, developing a value-for-money case with a protocol on collecting information. We present a set of five DES case studies from the US care system and, following Hollocks, focus on modelling as part of a rigorous design process, capturing as many of the benefits as possible. Healthcare offers the possibility of ascribing value to health improvement, but in these cases it is primarily the operational benefits of a better service that are reported and monetarised. By estimated the cost of modelling and the value of the operation gains, this paper contributes significantly to the literature. We conclude with a protocol for collecting information and a discussion of methods by which different types of benefit may be captured.